Prescribing errors involving antineoplastics and others drug centre of preparation of injectable drugs - Luciana SANTOS; Thalita JACOBY; Sandro NESS; Gérson GUERRA; Carlos A. WAYHS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To describe the prescribing errors involving antineoplastics and others drugs in a centre for the preparation of injectable drugs at a university hospital. Method: A retrospective descriptive study was carried out based on the records of a drug preparation center with prescribing errors identified in the pharmaceutical validation phase prior to drug preparation in the period from 2016 to 2017.Results: A total of 1516 prescriptions/month were evaluated and 562 prescribing errors were identified and the prescription error rate involving medications was 1.5%. Of the drugs most involved in errors are cisplatin (37.5%), etoposide (14.1%), carboplatin (8.9%), cyclophosphamide (5.7%) and oxaliplatin (4.1%). Most of the errors were related to the diluents associated with the preparations, either in the absence of this information or in the prescription of volumes outside the concentration range required by the preparation of the drug with 56% and 22.6% respectively. In 94.3% of the prescriptions identified with errors, pharmaceutical interventions were necessary for its correction before preparation with adhesion in 99.6% of the cases. Conclusion: Although prescribing errors are described in the literature, the study presents the fragility of the prescriber system, even when it is computerized, and the importance of organized barriers or processes to avoid errors of prescription and manipulation in a centre for the preparation of injectable drugs